Analysis of Lipid Yield from Chaetoceros calcitrans Microalgae Extract Using Gas Chromatography - Stepanus, Jamius Bin; Likumahwa, Fervin Mayos; Kesauliyaa, Olivia Marie Caesaria; Angrianto, Novaldi Laudi; Sumarna, Sabir; Islam, Muh. Fajar (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Renewable energy (RE) is a solution to the threat of the upcoming energy crisis. The increasingly massive energy transition is expected to significantly reduce the use of fossil fuels. Microalgae are one of the potential sources of RE for bioenergy (biodiesel) production due to their lipid content. This research was conducted to determine the percentage of lipid components; free fatty acids (FFA), monoglycerides (MAG), diglycerides (DAG), and triglycerides (TAG) in Chaetoceros calcitrans microalgae and to compare lipid yields using two extraction methods: Bligh-Dyer (wet samples) and Soxhlet extraction (dry samples).The results for C. calcitrans extracted using the Bligh-Dyer method showed that the percentage of lipid components (FFA, MAG, DAG, and TAG) ranged from 5.44% to 17.10%, with a total of 47.92%, and the lipid yield from 6 g of wet sample was 5.07%.Meanwhile, for the C. calcitrans extract using Soxhlet method, it was found that the percentage of lipid components (FFA, MAG, DAG and TAG) ranged from 6.79 to 18.01% with a total of 63.08% and the lipid yield from 20 g of dry samples was 0. 44%.